Campuran Pulp Tandan Kosong Kelapa Sawit dan Selulosa Mikrobial Nata de Cassava dalam Pembuatan Kertas - Khaswar Syamsu; Liesbetini Haditjaroko; Gamma Irca Pradikta; Han Roliadi (Institut Pertanian Bogor, 2014)
Nowadays, forest-extracted wood cellulose still predominantly serves as raw material for pulp and paper manufacture in Indonesia. Consequently, the deforestation rate has alarmingly increased. The purpose of this research is to study the use of mixed microbial cellulose pulp from nata de cassava and pulp from empty oil palm fruit bunch (EOPFB) for paper manufacture. In this research, pulp of nata de cassava’s microbial cellulose was mixed with EOPFB pulp at various proportions. Additives (i.e. 2% alum, 2.5% tapioca starch, and 5% kaolin) were added to such mixture. Sheet forming without additives was made as a control. Addition of microbial cellulose tends to increase the physical and strength properties of paper and decrease the capability to absorb water significantly. The mixture of pulp of empty oil palm fruit bunch and microbial cellulose from nata de cassava has a potency to substitute wood pulp for paper manufacture.